1996
DOI: 10.1515/humr.1996.9.3-4.363
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variance in current sense of humor inventories: How much substance, how much method variance?

Abstract: The present study investigates the relationship of self-report inventories of "sense of humor" and behavioral measures of humor as well as their location in the Eysenckian PEN system. 110 male and female adults in the ages from 17 to 83 years answered the following inventories: SHRQ (Martin and Lefcourt 1984), SHQZ (Ziv 1981), SHQ-3 revised (Svebak 1993), CHS (Martin and Lefcourt 1983), MSHS (Thorson and Powell 1993), HIS (Bell, McGhee, and Duffey 1986), 3 WD-K (Ruch 1983), CPPT (Köhler and Ruch 1993), TDS (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 31 publications
4
99
0
4
Order By: Relevance
“…The findings on psychoticism, extraversion, and neuroticism were in line with prior findings: while correlations of humour appreciation to E and N were absent, psychoticism related negatively to the funniness of INC-RES (Köhler & Ruch 1996). These results replicate findings from prior studies for the 3WD and show that the same patterns can be found for humour appreciation in TV advertisements.…”
Section: Personality Correlates Of Humour Appreciationsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings on psychoticism, extraversion, and neuroticism were in line with prior findings: while correlations of humour appreciation to E and N were absent, psychoticism related negatively to the funniness of INC-RES (Köhler & Ruch 1996). These results replicate findings from prior studies for the 3WD and show that the same patterns can be found for humour appreciation in TV advertisements.…”
Section: Personality Correlates Of Humour Appreciationsupporting
confidence: 89%
“…Psychoticism in Eysencks's view relates negatively to the funniness of incongruity resolution humour (e.g., Köhler & Ruch 1996). Extraversion predicts the liking of both structure factors, as well as the funniness of sexual humour (cf.…”
Section: Humour Appreciation and Personalitymentioning
confidence: 99%
“…For example, in the PEN model of personality, psychopaths are located on the Psychoticism-dimension (Eysenck & Eysenck 1976, 1978. In performance tests of humor creation, high P-scorers were found to be wittier than the low scorer (Köhler & Ruch, 1996). Pearson (1983) found higher P scorer among professional cartoonists, which could be interpreted as an indirect support for the notion of wittiness being associated with the psychopathy dimension.…”
mentioning
confidence: 83%
“…While McGhee (2010b) proposed six humor skills (i.e., enjoyment of humor, laughter, verbal humor, humor in everyday life, laughing at yourself, humor under stress), psychometric studies (Köhler & Ruch, 1996;Müller & Ruch, 2011;Ruch & Carrell, 1998) show that these components mostly mark a strong factor of humor that typically unites "[…] enjoying humorous stimuli, finding humour in everyday life and even in one's own mishaps, enjoying cheerful interactions and telling jokes" (Ruch & Carrell, 1998;p. 555).…”
Section: Developing Self-administered Humor-based Interventionsmentioning
confidence: 99%